El fracking como alternativa para la economía nacional. (2020)
Fracking is a hydrocarbon extraction technique that consists of injecting a fluid specially designed to break the rock in the subsoil and improve the permeability of the reservoir to increase the production of a project. Although this technique was invented in the 80`s, it reached its peak in recent years due to the fact that great hydrocarbon powers such as the United States began to implement it in great magnitudes to achieve its self-sufficiency, until it became the first oil producer worldwide. In the same way, countries that previously demanded a large quantity of hydrocarbons from abroad, such as China, and countries that are not so large but whose economy depends on oil, such as Chile or Argentina, begin to implement this technique, greatly increasing the offer of this natural resource. As a consequence, this produced that the price of a barrel of oil decreased significantly, putting the industry in crisis in countries that depend economically on a large percentage of oil exports, such as Colombia, generating a worrying scenario for the national economy, since all this devalues the Peso. with respect to the Dollar.